Expanding Searle’s analysis of interrogative speech acts: A systematic classification based on preparatory conditions - Nielsen, Niels Møller (Scandinavian Studies in Language, 2020)
In John Searle’s original taxonomy of types of illocutionary acts (Searle 1969) he points out that some kinds of illocutionary acts are special cases of other kinds, giving the example that questions are in fact special cases of requests. In that way, a ‘real question’ is a request for information that the sender does not already possess, whereas an ‘exam question’ is a request for information that the sender has already access to. This paper takes this rudimentary analysis some steps further and attempts a taxonomy of interrogative speech acts based on sets of more specific preparatory conditions such as sender expects / does not expect reply and sender has access to / does not have access to the requested information. The paper will show that a system of these sets of preparatory conditions can generate illocutionary definitions of a range of different types of interrogative speech acts.